Indonesian Presidential Election 2019 – State of Play : Who Will Win in Largest Single-Day Elections? - Arifianto, Alexander Raymond (2019)
Indonesia will conduct its general election on 17 April 2019. A simultaneous election of the presidency as well as the national and regional legislative chambers, it is the largest single-day democratic election in the world.